"Why are you here?" Seeking children's accounts of their presentation to Child and Adolescent Mental Health Service (CAMHS). (January 2016) - Stafford, Victoria; Hutchby, Ian; Karim, Khalid; O'Reilly, Michelle
The area of child mental health has a developing evidence base, with much of this focused on outcomes and a growing recognition for the value of process research. Despite this growth, however, there has still been little work conducted on first assessments in spite of their importance in establishing therapeutic rapport and engagement with services. We explore naturally occurring first assessments in a Child and Adolescent Mental Health Service (CAMHS) to explore the beliefs that children hold regarding their reasons for attendance and the implications this has for the trajectory of the appointment and later engagement with interventions. It was found that when children were asked for their reasons they either offered explanations using diagnostic labels or used lay descriptions, or they claimed to not know the reasons for attending the assessment. This has broader implications regarding the nature and type of information children may require in preparing them for service visits.